Functional studies on the chloroquine resistance transporter (PfCRT) and the HECT E3 ubiquitin-protein ligase (PfUT) in Plasmodium falciparum - Jankowska-Döllken, Monika (Ruperto Carola University Heidelberg, 2019)
Posttranslational modifications (PTMs) affect fundamental cellular functions of the human malaria parasite Plasmodium falciparum, including regulation of protein stability, metabolism, proliferation, apoptosis and signal transduction. This study investigates the importance of phosphorylation and ubiquitination in modulating the parasite intraerythrocytic development, as well as their implication in antimalarial drug resistance. The chloroquine resistance transporter PfCRT is a drug-metabolite carrier annotated as a prominent determinant of parasite’s reduced susceptibility to quinoline drugs. PfCRT is posttranslationally modified by phosphorylation and palmitoylation. However, the role of these PTMs in regulation of PfCRT function is not fully resolved. Chemical and genetic approaches employed in the current study revealed the relevance of PfCRT phosphorylation at serine 33 in regulating the drug resistance-mediating function of this transporter and in vitro fitness of the parasite. The PfCRT allelic exchange mutants, in which serine 33 was replaced by alanine showed increased sensitivity to chloroquine and quinine. Moreover, PfCRT serine 33 substitution by phospho-mimicking amino acids, glutamic and aspartic acid, could respectively partially and fully, restore the resistance phenotype. The fitness variation between the PfCRT mutants was linked to differences in merozoite numbers and their invasion efficiencies, with alanine mutants displaying a significant advantage in this regard. Identification of a kinase implicated in this phenomenon is desired, as its inhibition in combination with chloroquine could reduce or prevent the further spread of resistance. A HECT E3 ubiquitin ligase, termed ubiquitin transferase PfUT, is a novel candidate gene for multifactorial resistance to quinine. PfUT was shown to localize to the parasite’s ER/Golgi complex, but its role in reduced susceptibility to quinine and its physiological function remain unclear. Characterization of PfUT was attempted by a glmS ribozyme-based conditional knockdown of encoding it gene, generated using the CRISPR-Cas9 genome editing technology. Unexpectedly, integration of the glmS sequence resulted in a 2-fold increase in PfUT transcripts correlated with protein levels. PfUT overexpression, in turn, led to S phase-associated lengthening of parasite’s cycle, reflected in impaired growth. Glucosamine-induced incomplete downregulation partially restored the wild type phenotype. Moreover, the transgenic parasites exhibited an enhanced susceptibility to quinine and quinidine. An alternative disruption of the pfut locus via a selection-linked integration (SLI-TGD) strategy was unsuccessful, despite multiple attempts. These results underline the importance of PfUT in parasite proliferation and survival. However, a direct proof of PfUT’s association with quinine resistance and identification of its biological substrates await further investigation.
Keywords: Hochschulschrift